2019
DOI: 10.1515/tjb-2018-0341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some biochemical tests in different blood collection tubes in hemodialysis patients

Abstract: Objective Blood collection tubes (BCTs) related interferences in test results can adversely influence on patient outcomes. We compared test results of samples in BD (Becton-Dickinson, Franklin Lakes, NJ, USA) Vacutainer Serum Separator Tubes (SST), BD Vacutainer® Barricor™ Plasma BCTs (Barricor™) and BD Vacutainer® Rapid Serum Tube (RST). Materials and methods Thirty-two samples were obtained from patients after the hemodialysis were included in this study. Eight routine clinical chemistry parameters (AST, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
2
0
0
1
Order By: Relevance
“…Analyte results comparison given from both tubes were in line with our expectations and in agreement with previous examinations comparing serum and plasma specimen results (9,14-16 AST, LD and glucose in BD Barricor compared to serum samples (9). Difference in K concentration between plasma and serum tubes was observed in all mentioned studies (bias ranged from -4.9 up to -7.1%) and it was similar to the findings in our study (9,(14)(15)(16). Our study, together with all mentioned studies, found a higher bias for K than the one stated for desirability in both the EFLM Biological Variation Database or Westgard's database (11,12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analyte results comparison given from both tubes were in line with our expectations and in agreement with previous examinations comparing serum and plasma specimen results (9,14-16 AST, LD and glucose in BD Barricor compared to serum samples (9). Difference in K concentration between plasma and serum tubes was observed in all mentioned studies (bias ranged from -4.9 up to -7.1%) and it was similar to the findings in our study (9,(14)(15)(16). Our study, together with all mentioned studies, found a higher bias for K than the one stated for desirability in both the EFLM Biological Variation Database or Westgard's database (11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Analyte results comparison given from both tubes were in line with our expectations and in agreement with previous examinations comparing serum and plasma specimen results ( 9 , 14 - 16 ). Kosem et al compared eight biochemistry tests from BD RST and BD Barricor tubes with the BD Serum Separator Tubes (SST) as reference tubes ( 16 ). Their study was performed in haemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…The systematic error and proportional difference observed for the Ca, GGT, and INS analytes were not clinically significant, as all three tests remained within the BV %TEa limits (Table 1). Kösem et al 23 similarly interpreted their findings on parathormone. According to Ercan et al 14 the confidence interval for the CRP intercept did not contain a value of 0.…”
Section: Discussionmentioning
confidence: 76%
“…Produsen telah memproduksi berbagai tabung yang menyajikan pemisahan berkualitas tinggi antara serum atau plasma dan sel untuk mengurangi TAT dan mengurangi cellular intent (Kösem et al, 2020). Penelitian tentang penggunaan vacutainer serum separator ini juga sesuai dengan penelitian yang dilakukan oleh (Wei et al, 2010)…”
unclassified